SRL based Plagiarism Detection System for Malayalam Documents - Sindhu L and Sumam Mary Idicula (IJCSI International Journal of Computer Science Issues, 2015)
Automatic techniques of measuring plagiarism between documents have gained importance in the recent years because of the availability of enormous volume of information over the internet. . The most general form of detecting plagiarism is by computing similarity between a source document and a possibly plagiarised document. Existing plagiarism detection systems are mainly designed for detection in English.. Moreover, plagiarism detection systems using natural language processing techniques are still very limited. Automated plagiarism detection systems so far have involved minimal syntactic and semantic linguistic techniques. Even though, in some systems shallow techniques have been included as part of the pre- processing stage, studies involving deep techniquesIare less. Very negligible research has been done for plagiarism detection in Malayalam text documents . This paper presents a method for plagiarism detection in Malayalam documents based on extracting the semantic roles and computing their similarity to detect plagiarism. The technique can detect documents created by direct copy methods, replacement of words with similar ones , changing the order of words or restructuring the sentences and also converting the sentence from active/ passive to passive/active.